251 Communicating End of Life Care Decisions in an Acute Hospital. (16th September 2019) - Morrison, Laura; Clarke, Rebecca; McAteer, Claire; Dolan, Eamon; O'Connor, Marie
Abstract: Background: Research by the Irish Hospice Foundation reports 43% of Irish deaths occur in hospital. The aim of this study was to review in-hospital deaths in a university teaching hospital to examine whether escalation of care and resuscitation instructions were documented clearly where death was a likely outcome during hospitalisation. Methods: Medical records from 50 deaths in 2018 were reviewed. A proforma was designed to record detail on: demographics, if death was expected, and if resuscitation status, ceiling of care and discussion of these with the patient or family were clearly documented. Results: 50 patients were included, median age 83.5 years. In 84%, end of life was anticipated by the medical team. 74% of patients were seen by palliative care. The most common cause of death was pneumonia/respiratory sepsis (46%) and median length of stay was 13 days. 3 patients (6%) had cardiac arrest calls. A clear ceiling of care was recorded in 46% of cases. Goals of care were documented as discussed with the patient in 2% of cases and family in 78%. Resuscitation status was recorded as discussed with family in 62% and the patient in 4%. Resuscitation status was documented in 96% of cases; 60% by the primary team, 36% by on-call staff. In only 54% of cases the name, position and Medical Council number of the person recording resuscitation status were all clearly written. Resuscitation status was correctly documented on the Early Warning Score chart in 32% of cases. Conclusion: Clear documentation around treatment escalation plans is needed in patients admitted to an acute hospital. Resuscitation status and ceiling of care, if appropriate, should be decided and documented by the primary team where possible and discussed with the patient/family. This study showed a need to improve documentation and discussion with patients and families approaching end of life.